Pediatric Mesenchymal Hamartoma of the Liver: A Diagnostic Dilemma - Sahni, Manish; Daga, Ram; Jangir, Nishant; Singh, Suresh; Sharma, Rajgovind (Asian Pacific Journal of Cancer Care, 2023)
Background and objective: Benign liver tumors are relatively uncommon in children. Mesenchymal hamartoma (MH) is a benign liver tumor and the second most common benign pediatric hepatic tumor after infantile hemangioma. It is most frequently observed in children under 2 years of age. Diagnosis can be challenging due to non-specific clinical symptoms and the lack of definitive laboratory studies. Histological evaluation of tissue is essential for definitive diagnosis. This case report describes a rare case of mesenchymal hamartoma in a 2-year-old child, highlighting the diagnostic challenges. Case presentation: A previously healthy 2-year-old male was referred to our institution for evaluation of a liver mass. He suffered from a 10-week history of loss of appetite and abdominal distension. He reported no fever or trauma. Physical examination revealed a large, non-tender hepatomegaly without shifting dullness. Abdominal ultrasound showed a solitary right lobe mass. Further imaging with a CT scan of the abdomen revealed a large, multi-loculated lesion in the right lobe of the liver with arterial enhancing intervening septae. The lesion compressed and displaced the right portal vein and right hepatic vein. Laboratory evaluation revealed normal liver function tests, serum alpha-fetoprotein (AFP), and other blood parameters. Differential diagnoses included liver cyst, hydatid cyst, and biliary cystadenoma. After multidisciplinary discussion, a surgical approach was chosen to obtain a definitive histological diagnosis and address the cystic liver lesion. The patient underwent a right hepatectomy with r section of the 14 × 12 cm mass. No major peri-operative complications developed, and the patient was discharged on postoperative day 6. Pathological review of the resected mass revealed a mixture of bile ducts, vessels, irregular liver cell plates, and loose mesenchyme containing variable-sized cysts, consistent with mesenchymal hamartoma. The patient remains asymptomatic at follow-up. Conclusion: Benign liver tumors in children are relatively rare. The diagnosis of mesenchymal hamartoma can be challenging due to non-specific symptoms, normal laboratory findings, and potential for complications arising from local compression. Advanced imaging can be helpful, but differentiating it from other tumors such as undifferentiated embryonal sarcoma can be difficult based on imaging alone. Surgical excision remains the gold standard for definitive diagnosis and treatment.